Qanun Man’i al-Maysir fi Wilayati Aceh: Dirasatun Tahliliyatun fi Dhaui Maqasid al-Syari’ah (Mazahib, 2016)
This research aims to study the prevention law of gambling in Aceh. Which has applied since 2003 M. The problem appears from this study is miss understanding of some  Achiness society. Some of them accept that the gambling law is applied according to the purpose of Islam on the prohibit gambling. On another perception some of the community in Aceh do not accept it. they argue that the law of prevention gambling in Aceh is just from government not from Syari’. The explanation of appropriation between the purpose of government on applying this law and the purpose of maqashid al- syariah on prevention gambling. And discuss the reason of miss understanding society. So, this research will analyse the problems deal from this law, the solution, and finding out the wisdom of forbid gambling, and the relation prevention gambling law and the maqashid al – syariah on keep the wealth, because the command of preserve wealth is one of the purpose of syariah that Muslim should watch over it.thus, The researcher adopted the inductive methodology and the analytical approach to reach the solution on it. The most important result finding in this study is firm relation between the prevention gambling law in Aceh and maqashid al- syariah. Gambling is prohibited by many evidences and propositions from al-qur’an and hadits. In addition There are many kind of gambling renowned, the punishment for violate the gambling law is ta’ziriah. This forbidden relate to the command on keeping the wealth. Since that is one of the purpose of shariah. If the prevention of gambling law is approved and applied so that the purpose of shariah is reached as well. Futhermore, the law must be holdout on all Muslims to avoid gambling .